Cape Verde : Initial Assessment of the Formal Labor Market - World Bank (World Bank, 2012)
In the last 25 years, Cape Verde has made impressive progress in their historical transition from a centrally planned to market economy. Building the institutional foundations of a market economy, this small nation of islands located off the coast of West Africa has developed a vibrant private sector and opened to international trade. This has ignited economic growth, which in turn has brought about higher incomes and reduced poverty. Currently, Cape Verde has a well-functioning market economy and as a result graduated from the ranks of the low income countries to one of middle-income status. Such a successful transition, achieved over a short period of time, exceeded many observers' expectations. In any economy, the issue of high and persistent unemployment centers on the dynamics of net job creation linked to firm entry and firm expansion. The issue of disparities in labor market outcomes centers on the tendencies of reallocation of jobs and workers away from less productive regions, sectors and firms toward more productive economic activities. This study finds that in both fronts-net job creation and reallocation, there is reason for optimism. Job creation is substantially above job destruction. With respect to divergent labor market outcomes across islands, there is a trend towards convergence indicating that a national and integrated job market is emerging. Furthermore, as expected, these two developments are highly interlinked; emigration from areas and sectors characterized by relatively lower job growth and immigration into regions and sectors with relatively higher job growth is taking place. The study also offers preliminary findings about the effects of a public sector wage premium on labor market outcomes and, separately, there are indicative findings on factors that may be affecting the decision of workers to enter and stay in the informal sector or enter into formal employment.